Allenyl esters as quenching agents for ruthenium olefin metathesis catalysts. Issue 1 (4th January 2017) - Roy, Animesh; Silvestri, Maximilian A.; Hall, Robert A.; Lepore, Salvatore D.
Graphical abstract: Highlights: Allenyl esters cleanly arrested the activity of the ruthenium metathesis catalysts. These allenes are effective as mild catalyst quenching agents. The allenes also facilitated catalyst removal during purification. Abstract: In the attempt to synthesize substituted allenyl esters through a metathesis coupling of unsubstituted allenyl esters and alkenes using a variety of ruthenium catalysts, it was discovered that allenyl esters themselves cleanly arrested the activity of the catalysts. Further studies suggests possible utility of allene esters as general quenching agents for metathesis reactions. To explore this idea, several representative olefin metathesis reactions, including ring closing, were successfully terminated by the addition of simple allenyl esters for more convenient purification.